The immunobiology of the receptor of advanced glycation end-products: Trends and challenges - González-Bonet, Ileana (2017)
Pattern-recognition receptors have been highly conserved in evolution. They recognize danger signals including both pathogen- and damage-associated molecular patterns, also known as alarmins. Several signaling pathways leading to an inflammatory reaction as part of an effective defensive response, are thus triggered. RAGE, a receptor initially considered for advanced glycation end-products, is also known to be activated by several danger signals, thus functioning as a pattern-recognition receptor. As a new member of this family, attempts to unraveling its functioning show that RAGE activation not only results in innate immune response but also contributes to promote and shape the acquired immune reaction. As reported for other members of the family, RAGE presents many polymorphic variants and additional studies are needed to elucidate its significance in immune response and disease susceptibility. Here we describe recent advances unraveling RAGE functions, as well as its significance and challenges in immunobiology.